1997
DOI: 10.1292/jvms.59.587
|View full text |Cite
|
Sign up to set email alerts
|

Serum Apolipoprotein B-100 Concentrations in Healthy and Diseased Cattle.

Abstract: ABSTRACT. The purpose of this study was to establish the normal range of serum apolipoprotein B-100 (APO B-100) concentration in clinically normal cattle, and to assess its abnormalities with clinical diseases. We measured the serum concentration of APO B-100 in cattle of varying ages, breeds and sex, maintained under normal field conditions. Blood samples were obtained from 735 apparently healthy cattle and 146 cows with various diseases. The concentration of serum APO B-100 in cattle was assayed by the singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Of the days studied, plasma Apo-B 100 started to decrease 2 wks before calving, reached the minimum 3 d after calving, and then began to recover. Changes and concentrations of plasma Apo-B 100 match with those reported by Itoh et al (1997) and Myamoto et al (2006). Thus, modification in Apo-B 100 synthesis and secretion occurs coincident with fat accumulation that begins in the last 2-3 wks before calving and reach the maximum in the first wks of lactation (Bertics et al, 1992).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Of the days studied, plasma Apo-B 100 started to decrease 2 wks before calving, reached the minimum 3 d after calving, and then began to recover. Changes and concentrations of plasma Apo-B 100 match with those reported by Itoh et al (1997) and Myamoto et al (2006). Thus, modification in Apo-B 100 synthesis and secretion occurs coincident with fat accumulation that begins in the last 2-3 wks before calving and reach the maximum in the first wks of lactation (Bertics et al, 1992).…”
Section: Discussionsupporting
confidence: 79%
“…Serum Apo-B 100 is reduced when dairy cows approach parturition (Myamoto et al, 2006). The reduction of Apo-B 100 synthesis and secretion are generally related to liver excessive fat accumulation and dysfunction (Itoh et al, 1997). In our previous study (Bernabucci et al, 2004) we suggested that the decrease in mRNA for Apo-B 100 could be consistent with decreased synthesis and/or secretion of VLDL from liver during the periparturient period.…”
Section: Introductionmentioning
confidence: 90%
“…They reached their reference values that were reported by Mahley et al (1984) and Itoh et al (1997) in healthy cattle. These significant changes were not reported between the two diseased groups at any of the sampling days.…”
Section: Discussionsupporting
confidence: 68%
“…They have also used in biomembrane structures and as hormone precursors [ 12 ]. Thus, changes in plasma lipid levels affect other organ or tissue functions [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%